From research to the implementation of methods for the treatment and prevention of PTSD - Popiel, Agnieszka; Zawadzki, Bogdan (Przegląd Psychologiczny, 2021)
Objective Posttraumatic stress disorder (PTSD) affects approximately 10% of traffic accident victims and more than 50% of rape, war and violence victims. PTSD negatively affects the quality of life and is associated with direct and indirect costs in healthcare. Each of these reasons provide sufficient rationale for furthering research on effective treatment and prevention of PTSD. Thesis Between 2008 and 2018, the University of Warsaw and the SWPS University embarked on a series of research programs aiming to address vital social needs by determining the efficacy of the existing methods for the treatment and prevention of PTSD in individuals exposed to work-related trauma (the results can be used in healthcare planning). Conclusions Research results have important practical implications. Basic research examined the risk factors for PTSD and the structure of PTSD symptoms. Studies exploring the effectiveness of PTSD therapy have generated new knowledge about the comparative efficacy of psychotherapy, pharmacotherapy and combination therapy. The proposed cognitive therapy program was found to be as effective as prolonged exposure therapy without the need for trauma processing; therefore, it constitutes an alternative therapeutic method. The proposed method was used to develop the “Effective stress management” program that proved to be effective in preventing PTSD in individuals exposed to work-related trauma. A detailed protocol for replicating the methodology in other occupational groups exposed to trauma is available in the form of a manual. Published textbooks, educational activities and extensive training for professionals have increased the availability of treatment and prevention methods based on empirical data in Poland. The results of the research program have been cited in numerous foreign publications, and they have been incorporated into the NICE guidelines for the treatment of PTSD.